Analysis of analogous microbialite reservoirs and their associated petroleum systems in rift and passive margin basins: South Atlantic (Brazil) vs. North Atlantic (Portugal) - Barbosa, Gustavo Santana; Garcia, Gustavo Gonçalves; Barberes, Gabriel de Alemar; Pena dos Reis, Rui Paulo Bento; Garcia, Antônio Jorge Vasconcellos (Frontiers in Earth Science, 2025)
This study compares the efficiency of petroleum systems in the Santos Basin (Brazil) and the Lusitanian Basin (Portugal), focusing of the geological controls on hydrocarbon accumulation in two analogous microbialite reservoirs. We present a methodology integrating the static elements (source and reservoir rocks, seal, and trap) and dynamic elements (migration and accumulation, tectonic processes, thermal history, diagenesis) of petroleum systems with multiscale characterization from the basin to pore scale. Interpretive diagrams based on geological data analysis and a comparative table of static and dynamic elements were used to evaluate the analogous reservoirs and comprehensively analyze their potential. Salt tectonics played a critical role in the success of the Barra Velha Formation microbialite reservoirs in the Santos Basin, with the evaporite domes providing a highly effective seal for hydrocarbon trapping. In contrast, the Cabaços Formation microbialites in the Lusitanian Basin exhibit poor porosity due to pervasive diagenetic alteration (calcite recrystallization and mechanical compaction) observed at the petrographic scale. However, significant variations in lateral facies within these microbialites, observed at the outcrop scale, suggest potential for less diagenetically altered zones with improved reservoir properties and, consequently, better chances for hydrocarbon storage.